2017
DOI: 10.1001/jama.2016.21037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fibrinogen Concentrate on Intraoperative Blood Loss Among Patients With Intraoperative Bleeding During High-Risk Cardiac Surgery

Abstract: IMPORTANCE Fibrinogen concentrate might partly restore coagulation defects and reduce intraoperative bleeding.OBJECTIVE To determine whether fibrinogen concentrate infusion dosed to achieve a plasma fibrinogen level of 2.5 g/L in high-risk cardiac surgery patients with intraoperative bleeding reduces intraoperative blood loss. DESIGN, SETTING, AND PARTICIPANTSA randomized, placebo-controlled, double-blind clinical trial conducted in Isala Zwolle, the Netherlands (February 2011-January 2015), involving patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 39 publications
3
100
0
Order By: Relevance
“…Measured fibrinogen plasma levels were comparable to other previously published studies . Prophylactic and single‐dose administration of fibrinogen concentrate prevented fibrinogen plasma levels below 2g/L in the treatment group.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Measured fibrinogen plasma levels were comparable to other previously published studies . Prophylactic and single‐dose administration of fibrinogen concentrate prevented fibrinogen plasma levels below 2g/L in the treatment group.…”
Section: Discussionsupporting
confidence: 86%
“…Our original study design had to be modified because of a very slow recruitment rate due to screening failures. Despite having a simpler bleeding assessment compared with other fibrinogen studies, we encountered no diffuse bleeding after 44 patients . In addition, we changed the inclusion criteria to only patients with lower pre‐operative fibrinogen levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a higher proportion of blood transfusions in the hospital were found in the thrombocytopenic group. Operative patients with high blood loss experienced adverse outcomes 31. Second, the large epidemiological data revealed that thrombocytopenia itself may also directly affect prognosis 32.…”
Section: Discussionmentioning
confidence: 99%
“…Use of fibrinogen concentrate is indicated for treatment of inherited fibrinogen (factor I) deficiency in the U.S. and Europe, but results supporting for its use in response to trauma-related coagulopathy has not been demonstrated yet [33,34].…”
Section: ) Fibrinogen Concentratementioning
confidence: 99%